The Influence Of Transformational Leadership Style On Employee Performance At Bri Jennae Unit, Soppeng Regency - Andi Jenni Indriakati; Nurul Irma Sari; Jesica Ayu Pamula; Asmini Asmini; Puji Rahmah; Wahyulis Hersya (GENTARA: management and accounting research, 2026)
This study aims to determine the influence of transformational leadership style on employee performance at the BRI Jennae Unit, Soppeng Regency. This research employs a quantitative approach using a survey method. The population consists of all 13 employees of the BRI Jennae Unit, Soppeng Regency, with a saturated sampling technique applied. Data were collected through questionnaires using a Likert scale and analyzed using simple linear regression with the assistance of SPSS software. The results indicate that transformational leadership style has a positive and significant effect on employee performance, with a significance value of 0.001 (p < 0.05). This means that the better the implementation of transformational leadership style, the higher the employee performance at the BRI Jennae Unit, Soppeng Regency